2016
DOI: 10.1007/s00453-016-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

Sparsification Upper and Lower Bounds for Graph Problems and Not-All-Equal SAT

Abstract: We present several sparsification lower and upper bounds for classic problems in graph theory and logic. For the problems 4-Coloring, (Directed) Hamiltonian Cycle, and (Connected) Dominating Set, we prove that there is no polynomial-time algorithm that reduces any n-vertex input to an equivalent instance, of an arbitrary problem, with bitsize O(n 2−ε ) for ε > 0, unless NP ⊆ coNP/poly and the polynomial-time hierarchy collapses. These results imply that existing linearvertex kernels for k-Nonblocker and k-Max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A key result in this area is Schaefer's dichotomy theorem [20], which classifies each CSP over the Boolean domain as polynomial-time solvable or NP-complete. Continuing a recent line of investigation [12,14,17], we aim to understand for which NP-complete CSPs an instance can be sparsified in polynomial time, without changing the answer. In particular, we investigate the following questions.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A key result in this area is Schaefer's dichotomy theorem [20], which classifies each CSP over the Boolean domain as polynomial-time solvable or NP-complete. Continuing a recent line of investigation [12,14,17], we aim to understand for which NP-complete CSPs an instance can be sparsified in polynomial time, without changing the answer. In particular, we investigate the following questions.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This pessimistic state of affairs concerning nontrivial sparsification algorithms changed several years ago, when a subset of the authors [14] showed that the d-Not-All-Equal SAT problem does have a nontrivial sparsification. In this problem, clauses have size at most d and are satisfied if the literals do not all evaluate to the same value.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The problem Dominating Set takes as an input a graph G and an integer k, and the goal is to decide whether there exists X ⊆ V (G) of size at most k, such that for each v ∈ V (G), X ∩ N [v] = ∅. Jansen and Pieterse proved that Dominating Set does not admit a compression of bit size O(n 2− ), for any > 0 unless NP ⊆ coNP/poly, where n is the number of vertices in the input graph [15]. This result directly implies the following (see, for instance [1], for a formal statement).…”
Section: Lower Bounds On the Size Of Kernelsmentioning
confidence: 99%
“…Having presented the gadget we use in our construction, we define the source problem for the cross-composition. This problem was also used as the starting problem for a crosscomposition in our earlier sparsification lower bound for 4-Coloring [15]. [15] Input: A graph G with a partition of its vertex set into U ∪ V such that G[U ] is an edgeless graph and G[V ] is a disjoint union of triangles.…”
Section: Sparsification Lower Bound For 3-coloringmentioning
confidence: 99%
“…Our second main result concerns the parameterization by the number of vertices n. The current authors showed in earlier work [15] that for a number of graph problems it is impossible to give a kernel of size O(n 2−ε ), unless NP ⊆ coNP/poly. This implies that the number of edges cannot efficiently be reduced to a subquadratic amount without changing the answer, a task that is also known as sparsification.…”
Section: Introductionmentioning
confidence: 98%